Derivation of new clinical formulae and tricolor predicting chart for estimating birth weight at term - Ezike, Okolie Vitus; Betrand, Obi Nwosu; Azubuike, Obiechina Nwaorah Josiah; Zebulon, Okechukwu; Richard, Egeonu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Accurate fetal weight estimation is important for pregnancy and labor management. Clinical formulae are easy to use but have not been extensively studied. The use of the product of symphysiofundal height (SFH) and maternal abdominal girth (MAG) has been notorious for overestimating fetal weight, hence the need for its modification and production of pictorial chart for easy usage. The objective was to derive new Clinical Formulae and Tricolor birth weight predicting chart (TBPC) at term Methods: This is a cross sectional study done in the labor ward of Nnamdi Azikiwe University Teaching Hospital, (NAUTH) Nnewi, Nigeria between 1st July, 2011 and 31st December, 2011. A cross section of pregnant women at term with singleton who presented in labor ward for delivery was recruited for the study. The data collected were: the gestational age, maternal weight, MAG, SFH and birth weight (BW). Analysis was with SPSS version 16. Results: The new simple formula and the simple regression equation for predicting birth weight (BW) are BW = SFH (MAG - 7), (BW) =1000+ 0.7SFH (MAG- 7) respectively. TBPC was constructed for estimating birth weight. Conclusion: New formula, simple regression equation and TBPC are for birth weight estimation. The TBPC should be used in peripheral centers and referral made when necessary to a higher centre.